Fabrication and study of release kinetics of moxifloxacin and dexamethasone loaded nanostructured lipid carrier system for ocular drug delivery - Narayan Hemnani; Preeti K. Suresh (Creative Pharma Assent, 2025)
Background: The combination of moxifloxacin hydrochloride (MOX) and dexamethasone sodium phosphate (DEX) is widely available in the conventional commercial market for treating ocular infections and inflammations. Traditional ocular delivery systems are inferior to nanostructured lipid carriers (NLCs) due to their poor drug bioavailability, rapid tear drainage, and limited drug penetration. In contrast, NLCs offer sustained release, enhanced corneal absorption, and improved drug stability. Thus, the research aims to develop moxifloxacin and dexamethasone-loaded NLC for effective drug release. Methodology: In this study, a combination of MOX and DEX drugs was loaded in an NLC. The NLC was prepared using standard methods and evaluated for characteristic properties, including particle size (PS), polydispersity index (PDI), entrapment efficiency (EE), and drug loading (DL), as well as drug encapsulation and in vitro studies. Results and Discussion: The optimized formulation of NLC possessed a particle size of 190.58 nm and a polydispersity index of 26.7%. The fabricated drug exhibited a KP model release kinetics, indicating that drug release occurred via a combination of diffusion and polymer reaction. The NLC also exhibited a PDI of 26.7%, indicating a moderately uniform particle size distribution, which further suggests a consistent particle size, an acceptable characteristic for nano-carrier systems. The FT-IR analysis revealed optimal encapsulation of drugs inside the lipids, thereby achieving the desired objectives of drug fabrication. Conclusion: The formulated NLC has a particle size that falls within the ideal range for a smooth surface in commercial NLC formulations. Additionally, the prepared NLCs' adherence to the KP model underscores their potential as an advanced drug delivery system.